PENGARUH TOTAL ASET BANK TERHADAP POSISI BANK PADA INDEKS LQ45 - Roristua Pandiangan (Fakultas Ekonomi Universitas Borobudur, 2014)
The bank's financialhealthcan be seenfrom thebanks' balance sheetspublished by thebank itself, one of thebank's balance sheetprovidesinformationthat istotalassets. Banks thathavegood financialhealthcan provideareference forbusiness peoplewhowant toconducttransactions onthe bank'sissued shareson stock exchanges. This study examines theeffect oftotal bank assetsonthe bank's position on the sepesifikasi LQ45 comparative descriptive study. Source datafromthe Indonesia-Stock ExchangeandBanklndonesiaby usingsecondary data. The results show that: first, the influence ofthe total assets ofthe banktothe bank's positiononLQ45be disclosed. second, the total assets ofthe bankhad no effect onthe bank's positioninLQ45. Third, businesseshave not fullyincludetotal assetsas datain making decisionsfor tradingon the sharesof bankswith assetsin Indonesia. Fourth, bankstocksthathave thebiggest assetinlndonesiahas not fullyenthusedby the business. Key words : Total Assets, LQ45 Index